Substantial parallel mediation contribution by cognitive domains in the relationship between adolescents’ physical fitness and academic achievements: the Cogni-Action Project - Cristi-Montero, Carlos; Martínez-Flores, Ricardo; Espinoza-Puelles, Juan Pablo; Doherty, Anya; Zavala-Crichton, Juan Pablo; Aguilar-Farias, Nicolas; Reyes-Amigo, Tomas; Salvatierra-Calderon, Vanessa; Ibáñez, Romualdo; Sadarangani, Kabir P. (Frontiers in Psychology, 2024)
Objective: To determine how cognitive domains mediate the link between fitness components, their global score (GFS), and adolescents' academic achievement (ACA) across various school subjects. Methods: In this study, 1,296 adolescents aged 10-14 participated. GFS was computed by three fitness components (strength, muscular, and cardiorespiratory fitness) through the ALPHA-fitness test battery. ACA was determined by five school subjects (Language, English, Mathematics, Science, and History) and two academic scores a) "Academic Average" (five subjects) and b) "Academic-PISA" (Language, Mathematics, and Science). A principal component analysis was performed to establish four factors (working memory [WM], cognitive flexibility [CF], inhibitory control [IC], and fluid reasoning [FR]). A parallel mediation approach was implemented with 5,000 bootstrapped samples controlled for sex, maturity, central obesity, having breakfast before cognitive tasks, schools, and school vulnerability. Total, direct, indirect effects, and mediation percentages were estimated. Results: Overall, the finding showed a full parallel mediation effect for Language (92.5%) and English (53.9%), while a partial mediation for Mathematics (43.0%), Science (43.8%), History (45.9%), "Academic Average" (50.6%), and "Academic-PISA" (51.5%). In particular, WM, IC, and FR mediated all school subjects except mathematics, where IC was not significant. CF has not mediated any relationship between GF and academic performance.This study underscores the pivotal role of cognitive domains, specifically WM, IC, and FR, in mediating the link between physical fitness and academic performance in adolescents. These insights have relevant implications for educational and public health policies.